A Brief Introduction of Faiz Ahmad Faiz in the Perspective of His Poetry: Exploring the Life and Works of Faiz Ahmad Faiz (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present research paper is an attempt to introduce briefly the life and work of Faiz Ahmad Faiz, the one of the greatest revolutionary Urdu poets and innovative stylists. Although he is well known in Indo-Pak sub-continent for both his creative and polemical writings, he is largely unknown outside Asia, apart from certain fame in the former Soviet Union. Undoubtedly one important reason is the paucity of writings on him in other languages and his work’s translation, particularly in English, along with its critical evaluation in the context of the transforming socio-political condition of the colonial India, post-colonial Pakistan and finally in the context of the political affairs happened in the world beyond Pakistan.